2004
DOI: 10.1063/1.1827348
|View full text |Cite|
|
Sign up to set email alerts
|

Microstructural characterization of L1 FePt/MgO nanoparticles with perpendicular anisotropy

Abstract: L 1 0 FePt nanoparticles with perpendicular magnetic anisotropy were fabricated on a heated MgO substrate by using an atomic deposition technique. The microstructure of the FePt nanoparticles was studied by transmission electron microscopy and high resolution transmission electron microcopy. The as-made L10 FePt nanoparticles are isolated and have a faceted morphology with a bimodal distribution of particle size as small as 2.5 nm. A semicoherent atomic interface between the FePt nanoparticles and the MgO subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 19 publications
0
8
0
2
Order By: Relevance
“…Particles with the same magnetocrystalline anisotropy but different sizes will have different thermal stabilities (due to the different anisotropy energy per particle, E = K V, where V is the nanoparticle volume) and hence different coercivities. It was shown in a recent study [18] that particles with sizes as small as 3 nm could still adopt the fct structure; however, enhanced surface effects are expected to progressively modify the spin configuration [25] and, consequently, the hysteresis loop shape. [26] On the other hand, the degree of structural order and hence the magnetocrystalline anisotropy is known to depend on the Fe/Pt ratio.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Particles with the same magnetocrystalline anisotropy but different sizes will have different thermal stabilities (due to the different anisotropy energy per particle, E = K V, where V is the nanoparticle volume) and hence different coercivities. It was shown in a recent study [18] that particles with sizes as small as 3 nm could still adopt the fct structure; however, enhanced surface effects are expected to progressively modify the spin configuration [25] and, consequently, the hysteresis loop shape. [26] On the other hand, the degree of structural order and hence the magnetocrystalline anisotropy is known to depend on the Fe/Pt ratio.…”
mentioning
confidence: 97%
“…[15,16] Moreover, some progress towards the direct, one-step synthesis of tetragonal FePt particles (i.e., without first obtaining fcc nanoparticles) appears achievable via a recently reported polyol synthesis method [17] and by deposition on a substrate at elevated temperatures. [18] However, in spite of these significant efforts, preventing the undesired sintering during the fcc-fct phase transformation continues to be a significant challenge. The intermatrix synthesis is an alternative route to be explored for the one-step synthesis of tetragonal FePt particles.…”
mentioning
confidence: 99%
“…It was reported that some researchers attempted to obtain the granular microstructure by using various non-magnetic materials [2][3][4] . MgO is chosen for its widely application in the tunnel junction devices and has a suitable lattice mismatch with FePt (4%) [5][6][7] .In general, FePt-MgO nano-granular film can be formed by either FePt/MgO multilayer deposition or co-sputtering of FePt and MgO after the annealing [8][9] . Nevertheless, excessive amount of MgO non-magnetic phase will degrade the transformation of L1 0 -FePt [10] .…”
Section: Introductionmentioning
confidence: 99%
“…FePt 合 金 在 常 温 环 境 中 还 存 在 一 种 具 有 面 心 立 方 (face centered cubic, FCC)晶体结构的亚稳相(用A1表 示, 可以认为是高温相的过冷态), Fe和Pt原子随机出 现在格点位置, 不具备成分有序的特征. 在常温获得 的FePt薄膜通常都处于A1相, 需要经过适当的热处 理, 才能转变为更稳定的L1 0 相 [21,22] . A1-FePt也具有 铁 磁 性 , 但 立 方 磁 晶 各 向 异 性 能 很 低 .…”
unclassified